Analisis Kebangkrutan dengan Metode Altman Z-Score pada Sub Sektor Industri Kosmetik dan Keperluan Rumah Tangga yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017 Fakultas Ekonomi Universitas Batanghari Jambi - Indah Hairul Jannah (Universitas Batanghari Jambi, 2020)
What is not less important is in order to continue to survive (ovivive) in a realistic partnership, developing in a tighter corporate reputation where the company is more important in maintaining the sustainbility of its business with a variety of strategies that have been designed to keep it sustainable as a source of income. To find out the potential for bankruptcy and bankruptcy rating on companies using the Altman Z-score methode in cosmetics and household needs.can be seen in 2017, 3 companies that are non bankrupt namely PT. Martina Berto Tbk,PT.Mandom Indonesia Tbk,PT.Unilever Tbk and 2 companies that are bankrupt namely PT.Mustika Ratu Tbk,PT.Arkhsa Wira Internasional and the first rank is PT.Martina Berto Tbk.Form the result of the category ranking PT.Martina Berto Tbk, The category of bankruptcy is the highest rank of PT.Martina Berto Tbk because of the company, which never went bankrupt.